Candidate Proficiency Test Chemicals to Address Industrial Chemical Applicability Domains for in vitro Human Cytochrome P450 Enzyme Induction - Jacobs, Miriam Naomi; Kubickova, Barbara; Boshoff, Eugene (Frontiers in Toxicology, 2022)
Cytochrome P450 (CYP) enzymes play a key role in the metabolism of both xenobiotics and endogenous chemicals, and the activity of some CYP isoforms are susceptible to induction and/or inhibition by certain chemicals. As CYP induction/inhibition can bring about significant alterations in the level of in vivo exposure to CYP substrates and metabolites, CYP induction/inhibition data is needed for regulatory chemical toxicity hazard assessment. On the basis of available human in vivo pharmaceutical data, a draft Organisation for Economic Co-operation and Development Test Guideline (TG) for an in vitro CYP HepaRG assay that is capable of detecting the induction of four human CYPs (CYP1A1/1A2, 2B6, and 3A4), has been developed and validated for a set of pharmaceutical proficiency chemicals. However to support TG adoption, further validation data was requested to demonstrate the ability of the assay to also accurately detect CYP induction mediated by industrial and pesticidal chemicals, together with an indication on regulatory uses of the assay. As part of ‘GOLIATH’, a European Union Horizon-2020 funded research project on metabolic disrupting chemical testing approaches, work is underway to generate supplemental validated data for an additional set of chemicals with sufficient diversity to allow for the approval of the guideline. Here we report on the process of proficiency chemical selection based on a targeted literature review, the selection criteria and considerations required for acceptance of proficiency chemical selection for OECD TG development. (i.e. structural diversity, range of activity, relevant chemical sectors, global restrictions etc). The following 13 proposed proficiency chemicals were reviewed and selected as a suitable set for use in the additional validation experiments: tebuconazole, benfuracarb, atrazine, cypermethrin, chlorpyrifos, perfluorooctanoic acid, bisphenol A, N,N-diethyl-m-toluamide, benzo-[a]-pyrene, fludioxonil, malathion, triclosan, and caffeine. Illustrations of applications of the assay in relation to endocrine disruption and non-genotoxic carcinogenicity are provided.